Vicarious shame in a cross-cultural perspective: emotion concepts A.-S. SPANISH SHAME and Ger. FREMDSCHÄMEN/FREMDSCHAM - Kostiantyn I. Mizin; Liudmyla L. Slavova (Вісник університету ім. А. Нобеля. Серія Філологічні науки, 2024)
The article is devoted to revealing the cross-cultural specificity of the emotion of vicarious shame on the example of the German concept fremdschämen/fremdscham and the Anglo-Saxon spanish shame. The study aims to identify those cultural factors that led to the most noticeable differences in the conceptual structures of emotion concepts of Ger. fremdschämen/fremdscham and A.-S. spanish shame. To meet this objective, a three-stage methodology was developed, which was based on the use of interdisciplinary research tools (traditional linguistics, cognitive and corpus linguistics), as well as the involvement of data from psychology, anthropology, and sociology. Strengthening the cross-cultural analysis with the empirical data of language corpora made it possible to reveal divergences in the conceptual structures of the concepts of A.-S. shame and Ger. scham, which are the base for such derivatives as spanish shame and fremdschämen/fremdscham. A selection of the most relevant English lemmas Eng. shame and Germ. Scham is performed on the basis of two frequency indicators – (1) the combinability of these lemmas (Freq.) and (2) the typicality (regularity) of this combinability (logDice/MI-index). On the conceptual level Freq. is an indicator of the relevance of a concept in a certain linguistic community, and logDice/ MI-index are indicators of the collocational strength, i.e. the invariability of the compatibility of this concept with other concepts. The proposed methodology made it possible to reveal divergences in the conceptual structures of the concepts of A.-S. shame and Ger. scham, which are the base for such derivatives as spanish shame and fremdschämen/fremdscham. It was established that these differences led to different approaches to the cross-cultural transfer of the Spanish “foreign” (vicarious) shame, represented by the emotion concept of vergüenza ajena, to German and Anglo-Saxon culture. Divergences were established against the background of two criteria for dividing cultures: “cultures of shame – cultures of guilt” and “individualism – collectivism” because these criteria are closely correlated with concepts representing the emotion of shame and its varieties. A certain correlation of the concepts of A.-S. shame and Ger. scham with the level of individualism in the respective cultures has been established, since a higher individualism index in Anglo-Saxons and a lower one in Germans somewhat influenced the external sanctioning of shame. In the Anglo-Saxon culture, a high index of individualism determined the greater privacy of shame, which brought the concept of shame closer in terms of sanctioning to guilt. Therefore, in the English-speaking environment, the connection between the concepts of shame and guilt is of significant relevance, which emphasizes that the Anglo-Saxons belong to the “guilt culture”. However, the shame that an individual empathically experiences in a situation of shameful acts or the shameful behaviour of a stranger is not private, since it is based solely on external sanctioning. Therefore, “foreign” (vicarious) shame, to some extent, does not agree with the “individualistic” nature of Anglo-Saxon shame. This divergence between shame and vicarious shame led to the establishment of the association of “foreign” (vicarious) shame with the Spaniards in the English-speaking environment. As a result, the emotion concept of spanish shame was formed. But among the Germans, who also belong to the “guilt culture”, shame is not private but public, i.e., it has a distinctive external sanctioning. This means that, unlike shame and spanish shame, German concepts of scham and fremdschämen/fremdscham are entirely consistent in terms of sanctioning. Therefore, in the German linguo-society, ethnic and socio-cultural restrictions did not arise during the transfer of the Spanish concept vergüenza ajena.